Multi-omics integration identifies molecular markers and biological pathways for carcass and meat quality traits in Nellore cattle - Frezarim, Gabriela B. [UNESP]; Mota, Lucio F. M. [UNESP]; Fonseca, Larissa F. S. [UNESP]; Salatta, Bruna M. [UNESP]; Arikawa, Leonardo M. [UNESP]; Schmidt, Patrícia I. [UNESP]; Silva, Danielly B. S. [UNESP]; Albuquerque, Lucia G. [UNESP] (Springer Nature, 2025)
Understanding the biological factors that influence carcass and meat quality traits in Nellore cattle requires a clear interpretation of molecular complexity and its variations at different levels of expression. Hence, this study aimed to elucidate the biological control of carcass and meat quality traits in Nellore cattle by integrating genome-wide association study (GWAS), transcriptomic, and proteomic data, focusing on identifying key genes and pathways. GWAS analysis was performed using weighted single-step GBLUP with two iterations. RNA-Seq and proteomic analyses were performed on 24 muscle samples from animals with divergent adjusted phenotypic values (12 for high and 12 for low), for meat tenderness, ribeye area (REA), marbling, and backfat thickness (BFT). The phenotypic values were adjusted for the systematic effects of contemporary groups and age. Differential expression analyses indicated that genes associated with the promotion of growth processes, such as FRZB, IGFBP5 and SEMA6C, exhibited overexpression within the group characterized by higher meat tenderness that inhibits cellular cycles and growth (RTN4 and RB1) were downregulated. Proteins related to heat shock, structural functions, and metabolic regulation also affected the higher meat tenderness group. For marbling, actin-binding proteins, microtubule-forming proteins, and structural proteins were downregulated, while genes involved in fatty acid composition and synthesis were upregulated, with the key genes and transcripts CAND1, ACTN4, FGFR2, and NCOR2 identified. For BFT, neuronal genes, transcripts, and proteins associated with actin cytoskeleton organization and microtubule formation were found. Key genes related to ubiquitination, regulation of energy metabolism, and tissue remodeling were also identified. These findings provide a better understanding of genes, transcripts, proteins, and metabolic pathways involved in carcass and meat quality traits in Nellore cattle.